Undiagnosed traumatic diaphragmatic hernia in two cats - Lau, Seng Fong (Veterinary Association Malaysia, 2016)
Two cases of diaphragmatic hernia in cats caused by road traffic accident were undiagnosed during the initial presentation. Both cats showed no evidence of respiratory distress and clinicians did not notice the diaphragmatic hernia on thoracic radiographs. Later on, both cats showed signs of dyspnea and diaphragmatic hernia was diagnosed with repeated thoracic radiograph and ultrasound. Diaphragmatic hernia is rather common in veterinary practice, however, its diagnosis can be clinically challenging. This case report highlights the importance to re-evaluate and monitor the patient closely after the traffic accident. Repeated radiograph, different diagnostic modalities and techniques such as ultrasound, computed tomography and positive contrast peritoneagraphy should be used in order to diagnose the diaphragmatic hernia conclusively.